Perception on penan's oroo’ language among local community at Batu Bungan, Mulu, Sarawak, Malaysia - Ibrahim, Mohamad Syahrul Nizam; Adam Assim, Mohd Ibrani Shahrimin; Johari, Shazali; Wan Mohammad, Syarifah Kamariah; Hassan, Suziana (2021)
Oroo’ secret sign language is a medium that has been used to communicate in the forest among Penan community. It is threatened language and identified as living cultural heritage that has high potential to be promoted as a major tourism product in the World Heritage Site, Mulu. However, the local level appreciation on their cultural elements is a question that would have implications for this language to become extinct imminently. Thus, this study aims to examine perception on the importance of Oroo’ language among Penan community at Batu Bungan. This exploration was conducted through a qualitative approach with personal interview with two Penans who are tribal chief and boatman who lived at the settlement. They were identified as key informants due to their active involvement and grown in the community. The narrative was analysed by thematic analysis deductively to elucidate their views on importance of Oroo’ secret sign language in the community today. It was found that most young generation did not understand the language due to some factors. They perceived that Oroo’ has no significant to their life because words are main medium of communication nowadays. While middle-aged community has at least basic knowledge of Oroo’ from their self-experience with old-aged generation in the forest. The language is threatened with extinction due to its significant declining users. There is a need for relevant stakeholders to take actions towards preserving this intangible and unique cultural heritage.